2020
DOI: 10.1186/s40170-020-00216-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning the metabolic rewiring and adaptation of translational machinery during an epithelial-mesenchymal transition in breast cancer cells

Abstract: Background: During breast cancer progression, the epithelial to mesenchymal transition has been associated with metastasis and endocrine therapy resistance; however, the underlying mechanisms remain elusive. To gain insight into this process, we studied the transition undergone by MCF7-derived cells, which is driven by the constitutive nuclear expression of a MKL1 variant devoid of the actin-binding domain (MKL1 ΔN200). We characterized the adaptive changes that occur during the MKL1-induced cellular model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…We recently reported that EMT-like MKL1 ΔN200 cells show extensive molecular and biochemical modifications (Fernández-Calero et al, 2020). Indeed, our transcriptomic and translatomic results suggest a general boost in translation that could be sustained by the significant increase in the expression and activity of several components of the protein synthesis machinery and translation-associated factors (Fig.…”
Section: Main Textmentioning
confidence: 57%
See 2 more Smart Citations
“…We recently reported that EMT-like MKL1 ΔN200 cells show extensive molecular and biochemical modifications (Fernández-Calero et al, 2020). Indeed, our transcriptomic and translatomic results suggest a general boost in translation that could be sustained by the significant increase in the expression and activity of several components of the protein synthesis machinery and translation-associated factors (Fig.…”
Section: Main Textmentioning
confidence: 57%
“…In addition, MKL1 ΔN200 cells display deep metabolic rewiring consistent with an enhanced Warburg-like effect characterized by impairment of Tricarboxylic Acid Cycle (TCA), rise of glucose consumption and glycolysis, flux redirection towards oxidative steps of the Pentose Phosphate Pathway (Fig. 1) (Fernández-Calero et al, 2020). This behavior was also detected in different cellular models of EMT (Kondaveeti et al, 2015;Liu et al, 2016;Morandi et al, 2017;Martínez-Reyes and Chandel, 2020).…”
Section: Main Textmentioning
confidence: 60%
See 1 more Smart Citation
“…Metabolic adaption is an adaptive change occurring during the cells in response to silica under the p53-existing or deficiency status. The final goal of this adaptive change is to achieve a new homeostatic status and maximize the opportunity for cell survival [ 32 ]. In total, 42 metabolites changed significantly in HBE p53-KO cells compared with p53-wt cells ( p < 0.05), of which 22 were upregulated and 20 were downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic adaption is an adaptive change occurring during the cells in response to silica under the p53-existing or de ciency status. The nal goal of this adaptive change is to achieve a new homeostatic status and maximize the opportunity for cell survival [32]. In total, 42 metabolites changed signi cantly in HBE p53-KO cells compared with p53-wt cells (p < 0.05), of which 22 were upregulated and 20 were downregulated.…”
Section: De Ciency Of P53 Signi Cantly Alters Silica-mediated Metabolmentioning
confidence: 99%